2002
DOI: 10.1097/01.mp.0000024291.37651.cd
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and In Situ Viral Findings in the Myocardium in Cases of Sudden, Unexpected Death

Abstract: The purpose of this study was to do in situ viral detection in myocardial tissues of individuals who suffered sudden unexpected death and to correlate the results with the postmortem histopathologic findings. Thirteen cases were identified and the heart tissues were analyzed for adenovirus, cytomegalovirus, Epstein Barr virus, herpes simplex vi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 25 publications
1
55
1
Order By: Relevance
“…The presence of replicating rotavirus in lung macrophages and the correlation of detecting rotavirus in both the lungs and hearts of RRVinoculated rat pups (P Ͻ 0.001; r ϭ 0.801 [Pearson's correlation coefficient]) are of interest. In cases of fatal pneumonitis, myocarditis, or sudden, unexpected death in adults and children, rotavirus antigen or RNA was detected in infiltrating macrophages, endothelial cells, and pneumocytes (11,35,41). Altogether, our data indicate that detection of rotavirus in the heart and lungs appears to be a rare event, but further studies are warranted to assess the involvement of rotavirus with pulmonary complications and myocarditis.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The presence of replicating rotavirus in lung macrophages and the correlation of detecting rotavirus in both the lungs and hearts of RRVinoculated rat pups (P Ͻ 0.001; r ϭ 0.801 [Pearson's correlation coefficient]) are of interest. In cases of fatal pneumonitis, myocarditis, or sudden, unexpected death in adults and children, rotavirus antigen or RNA was detected in infiltrating macrophages, endothelial cells, and pneumocytes (11,35,41). Altogether, our data indicate that detection of rotavirus in the heart and lungs appears to be a rare event, but further studies are warranted to assess the involvement of rotavirus with pulmonary complications and myocarditis.…”
Section: Discussionmentioning
confidence: 82%
“…Rotavirus antigen and RNA were detected in serum samples from approximately 65% of children with rotavirus diarrhea, indicating that antigenemia and possibly viremia occur during rotavirus infection (4, 7, 16). In other reports, rotavirus antigen and/or RNA was detected in the central nervous systems, spleens, hearts, kidneys, testes, and bladders of children who died during rotavirus infections (23, 29-32, 35, 42); in liver biopsies from infants with cholestatic disease (47); and in respiratory secretions, lung cells, or the microvasculature of hearts from children and adults with respiratory infections or cardiorespiratory failure (11,41,48,56) and rotavirus gastroenteritis. These case reports support the concept that rotavirus can escape the intestine and possibly infect cells in a variety of organs, but the sites and prevalence of extraintestinal infection and whether rotavirus can be the etiologic agent of extraintestinal disease have not been established.…”
mentioning
confidence: 99%
“…Whether putative central nervous system (CNS) infection results from contamination is not known, but one study strongly suggested infection of the CNS (48). In recent studies, rotavirus antigens were detected in myocardium from patients who died unexpectedly (11), and in vitro studies demonstrated the ability of rotavirus to replicate in primary islet cells, an observation that correlates with the temporal association of infection with development of pancreatic islet autoantibodies (14). These case reports strongly indicate that rotavirus infection may have rare systemic sequellae, although one must bear in mind that infectious viruses were not isolated and replication was shown only once (26).…”
Section: Systemic Infection With Rotavirusmentioning
confidence: 93%
“…With regard to the time-dependent course of viral myocarditis, as studied in a mouse model, early virus-induced myocardial damage already takes place before histologic and immunohistochemical signs of myocarditis defined by the Dallas criteria can be observed (23,24). These early-phase-dependent viral lesions can be detected only via electron microscopy; they also occur before immunohistochemical signs of myocarditis (19).…”
Section: Discussionmentioning
confidence: 99%